1989
DOI: 10.1159/000226699
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Mitoxantrone Cytotoxicity by Verapamil in Human Chronic Myeloid Leukemia Cells

Abstract: Calcium channel-blocking agent verapamil has been established to be an effective drug to modulate the action of many anticancer drugs. In this study, we examined the effect of verapamil on the cytotoxicity of mitoxantrone in human chronic myeloid leukemia (CML) cells. Mitoxantrone alone exhibited dose-dependent inhibition of DNA biosynthesis in CML cells. The addition of verapamil (3.3 μM) enhanced the responsiveness of CML cells to mitoxantrone (1 μg/ml) cytotoxicity indicated by significant increased inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…22]. Various compounds which are clinically utilised in ailments other than cancer, such as verapamil [7,10,23], trifluoperazine [11], nitroxazepine [24] and chloimipramine [25] have been shown to potentiate the activity of Adr in both drug-sensitive and drug-resistant cells. Tween 80 has also been shown to enhance the efficacy of various antitumor agents in vitro and in vivo, in experimental tumor models [14,15], Kerr et al [16] have recently reported that B-30 enhances the cellular uptake of Adr and improves the cytotoxicity of Adr in monolayer, clonogenic and spheroid culture systems.…”
Section: Effect O F B-30 and B-35 On A Dr Cytotoxicity In S I80 And Ementioning
confidence: 99%
“…22]. Various compounds which are clinically utilised in ailments other than cancer, such as verapamil [7,10,23], trifluoperazine [11], nitroxazepine [24] and chloimipramine [25] have been shown to potentiate the activity of Adr in both drug-sensitive and drug-resistant cells. Tween 80 has also been shown to enhance the efficacy of various antitumor agents in vitro and in vivo, in experimental tumor models [14,15], Kerr et al [16] have recently reported that B-30 enhances the cellular uptake of Adr and improves the cytotoxicity of Adr in monolayer, clonogenic and spheroid culture systems.…”
Section: Effect O F B-30 and B-35 On A Dr Cytotoxicity In S I80 And Ementioning
confidence: 99%
“…Anthraquinone compounds, especially daunoribicin, doxorubicin, epirubicin and mitoxantrone, are the most effective clinical anticancer medications (21). Mitoxantrone, with its planar anthraquinone structure, is a clinically useful antineoplastic agent (22)(23)(24)(25)(26)(27)(28) SZ-685C, one of sea anthraquinone metabolites, represses human breast cancer and human nasopharyngeal carcinoma cells (29). Anthraquinones have high antitumor effect.…”
Section: Introductionmentioning
confidence: 99%